2002
DOI: 10.1002/app.10665
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable polyester composites reinforced with short abaca fiber

Abstract: ABSTRACT:The mechanical properties of poly(3-hydroxybutyrate-co-3-hydroxyvarelate) (PHBV) composites, reinforced with short abaca fibers prepared by melt mixing and subsequent injection molding, were investigated and compared with PHBV composites reinforced with glass fiber (GF). The influences of fiber length, fiber content, and surface treatment of the natural fiber on the mechanical properties were evaluated. Regarding fiber length, the tensile properties had a maximum at a fiber length of about 5 mm. The f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
114
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(122 citation statements)
references
References 20 publications
8
114
0
Order By: Relevance
“…This reduction was probably caused by the restricted chain mobility of the PLA molecules or simply because of the weight reduction as a result of fibre addition. No significant effect was observed after fibre addition, and the same observation has been obtained by other researchers (Mishra et al 2002;Shibata et al 2002;Lee et al 2008). They reported that the addition of a small amount of cellulose fibres to the PLA matrix did not lead to a change in Tg.…”
Section: Differential Scanning Calorimetry (Dsc)supporting
confidence: 85%
“…This reduction was probably caused by the restricted chain mobility of the PLA molecules or simply because of the weight reduction as a result of fibre addition. No significant effect was observed after fibre addition, and the same observation has been obtained by other researchers (Mishra et al 2002;Shibata et al 2002;Lee et al 2008). They reported that the addition of a small amount of cellulose fibres to the PLA matrix did not lead to a change in Tg.…”
Section: Differential Scanning Calorimetry (Dsc)supporting
confidence: 85%
“…Investigation on changes in mechanical properties as a function of lignocellulosic fiber diameter has been reported since more than four decades [24][25][26][27][28][29][30] . Earlier international research groups investigated coir 24 , banana 25 , sisal 26 , pineapple 27 , palmyrah and talipot 28 fibers.…”
Section: Abstract: Fique Fiber Elastic Modulus Weibull Analysis Hymentioning
confidence: 99%
“…In these earlier works no correlation was proposed for the variation of mechanical properties with fiber diameter. More recently [29][30][31][32][33][34][35][36] it was found for several lignocellulosic fibers that both tensile strength and elastic modulus decrease as the fiber diameter increases. In particular, Biagiotti et al 31 were the first to indicate a mathematical expression using the Griffith model:…”
Section: Abstract: Fique Fiber Elastic Modulus Weibull Analysis Hymentioning
confidence: 99%
“…Furthermore, the results of an Izod impact test showed that the impact strength improved from 4.4 kJ/m 2 to 7.8 kJ/m 2 when a plasticizer was added to PLA resin prior to fabrication of the composites. Shibata et al (4) (5) also developed green composites reinforced with abaca fibers using injection molding. Abaca fibers were cut to 3-7 mm length with average diameter of 0.2 mm.…”
Section: Short-fiber Green Compositesmentioning
confidence: 99%